Quadruple Helix Strategy in Increasing the Quality of Human Resources (HR) in the Creative Industry of Muslim Fashion in Binjai - Haya, Salwa Fadhilah; Ahmadi Bi Rahmani, Nur; Syarvina, Wahyu (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2023)
Collaboration among government actors, academics, business owners, and the community is needed in the strategy to increase the workforce for the Muslim fashion industry in Binjai City. This study aims to analyze the roles and relationships of each actor in improving fieldwork in Binjai. This research method is qualitative with a Quadruple helix approach in realizing an increase in the creative industry workforce in the Muslim fashion sector in Binjai. The results of this study indicate that the Quadruple Helix actors involved in absorbing labor in the Muslim fashion industry, namely the roles of stakeholders such as universities, business people, and the community, have multiplied. At a time when the government’s role in the development of the fashion business is growing, the creative industry workforce is still not running optimally. The synergy between these stakeholders has been going well, both are mutually beneficial. The strategy between the Quadruple helix has been going well, through Segmenting, Targeting, and positioning, how to promote with promotional media users.